Population pharmacokinetics of mycophenolic acid in pediatric renal transplant patients using parametric and nonparametric approaches - Prémaud, Aurelie; Weber, L. T.; Tönshoff, Burkhard; Armstrong, V. W.; Oellerich, M.; Urien, S.; Marquet, P.; Rousseau, A. (Pharmacological research, 2011)
Mycophenolic acid (MPA) is an immunosuppressive drug widely used in the prevention of acute rejection in pediatric renal transplant recipients and is characterized by a wide inter-individual variability in its pharmacokinetics. The aim of this study was to compare population pharmacokinetic modeling of MPA in pediatric renal transplant recipients given mycophenolate mofetil, the ester prodrug of MPA, using parametric and nonparametric population methods. The data from 34 pediatric renal transplants (73 full pharmacokinetic profiles obtained on day 21, months 3, 6 and 9 post-transplant) were analyzed using both the nonlinear mixed-effect modeling (NONMEM) and nonparametric adaptive grid (NPAG) approaches, based on a two-compartment model with first order lagged time absorption and first order elimination. The predictive performance of the two models was evaluated in a separate group of 32 patients. Higher mean population parameter values and ranges of individual pharmacokinetic parameters were obtained with NPAG, especially for the elimination constant ke: mean 1.16 h(-1) (0.26-4.33 h(-1)) and 0.78 h(-1) (0.66-1.15 h(-1)) with NPAG and NONMEM, respectively. With NPAG, the skewness and kurtosis values for ke (2.03 and 7.80, respectively) were far from the theoretical values expected for normal distributions. Such a non-normal distribution could explain the high value of shrinkage (35%) obtained for this parameter with the parametric NONMEM method. Bayesian forecasting of mycophenolic acid exposure using the NPAG population pharmacokinetic parameters as priors yielded a better predictive performance, with a significantly smaller bias than with the NONMEM model (-1.68% vs -9.53%, p<0.0001). In conclusion, in the present study, NPAG was found to be the most adequate population pharmacokinetic method to describe the pharmacokinetics of MPA in pediatric renal transplant recipients.
Available online 5 November 2010
Gesehen am 13.01.2023